(3GdeYQGLs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3gPg QSGdI ef JUGfja GdQGRi HGH ai GdeYQGL hajg aUhd GdaUd GdChd ai HjGf ecGfg GYde Gf GdeYQGL eYQGL ef ecI Edi HjJ GdebOS s
(3BNQgG (B:s
(3aGTJZd HGdOYhI aGPG abO UHQc aGTJZd HGdUdGI jG CjgG GdeOKQ be aGfPQ hQHc acHQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(3/1035) s
Keywords: (3GdJhMjO hGdedd hGdfMds